Efficacy of Proveblue (Methylene Blue) in an Experimental Cerebral Malaria Murine Model - Dormoi, Jérome (American Society for Microbiology, 2013)
Although 100% of untreated mice infected with Plasmodium berghei died with specific signs of cerebral malaria and 100% of mice treated with 3 mg/kg dihydroartemisinin, the active metabolite of artesunate, which is used as the first-line treatment for severe malaria, also died but showed no specific signs of cerebral malaria, 78% of mice treated with 10 mg/kg Proveblue (methylene blue) and 78% of mice treated with a combination of 3 mg dihydroartemisinin and 10 mg/kg Proveblue survived and showed no specific signs of cerebral malaria or detectable parasites.